(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This paper presents a mathematical model of electropneumatic positioning system including the length of pneumatic lines for the determination of flow and pressure in unsteady operating modes. A simulation model is developed to study the dynamic processes in an electropneumatic positioning system. Simulation of the mathematical models of the screw compressor, proportional directional valve, pneumatic lines, pneumatic cylinder and PID controller were designed in “MatLab Simulink”. The simulation models of the transients in the electropneumatic positioning system at different line lengths from 1m and 10m with stepwise variation of the input setpoint are simulated developed. Graphical comparison is made of the obtained experimental results and simulation model influence of the pneumatic line length on the dynamics of the electropneumatic positioning system are made.